Fast curing flexible conductive one component (1K) epoxy adhesive composition

By using conductive compositions containing alicyclic epoxy resin and vinyl ether in the photovoltaic module, the problem of poor electrical contact stability of conductive adhesives in high humidity and low temperature environments is solved, and rapid curing and high mechanical strength are achieved , improves the long-term reliability of photovoltaic modules.

CN119317680APending Publication Date: 2025-01-14HENKEL KGAA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380043471.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2023-05-09
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing conductive adhesives accumulate mechanical stress caused by mismatch in photovoltaic modules, resulting in a decrease in the module life, long curing time and poor flexibility, making it difficult to maintain stable electrical contact in high humidity and low temperature environments.

Method used

Used to contain 5-25% alicyclic epoxy resin, 0.05-10% vinyl ether, 0.1-0.45% onium salt, 0.01-10% free radical initiator, 45-85% conductive particles and 0.1-10% organic solvent The conductive composition achieves high processing volume and flexibility through rapid curing and low curing temperature.

Benefits of technology

The conductive composition that maintains stable electrical contact in low temperature and high humidity environments is achieved, and the mechanical strength and long-term reliability performance of the photovoltaic module are improved, and the curing time and volume resistivity are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005157950170000091
    Figure BDA0005157950170000091
  • Figure BDA0005157950170000101
    Figure BDA0005157950170000101
  • Figure BDA0005157950170000102
    Figure BDA0005157950170000102
Patent Text Reader

Abstract

The present invention relates to an electrically conductive composition comprising: a) from 5 to 25% by weight, based on the total weight of the composition, of an alicyclic epoxy resin; b) from 0.05 to 10 wt%, based on the total weight of the composition, of a vinyl ether; c) from 0.1 to 0.45% by weight of an onium salt based on the total weight of the composition; d) 0.01 to 10 wt%, based on the total weight of the composition, of a free radical initiator; e) from 45 to 85% by weight of conductive particles based on the total weight of the composition; and f) 0.1 to 10% by weight of an organic solvent based on the total weight of the composition. The composition can be used as an adhesive in electronic applications, in particular as an adhesive in shingled module photovoltaic applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a fast-curing flexible conductive one-component (1K) epoxy adhesive composition. The composition is suitable for use as an adhesive in electronic applications, in particular as an adhesive in shingled module photovoltaic applications. Background Art

[0002] A solar cell or photovoltaic cell is an electrical device that converts light energy directly into electrical energy through the photovoltaic effect. Solar cells are a component of photovoltaic modules, also known as solar panels.

[0003] like Figure 1 As illustrated, most solar cells (1) produced today consist of a crystalline silicon wafer with printed metal contacts - bus bars (2) and fingers (3) - that are used to collect the current generated by the cell. For illustration purposes only, Figure 1 a shows a basic solar cell configuration with three bus bars (2), Figure 1 b shows a basic solar cell configuration with four bus bars (2).

[0004] An array of linear, parallel and equally spaced thin fingers (3) covers a small portion of the light receiving surface of each individual silicon solar cell (1). These finger lines (3) reduce the resistance to the photoelectric current and provide lower current loss. In addition, the finger lines (3) collect the current from the surface of the silicon solar cell and transmit it to the tabbing ribbon (5) (such as bus bars (2)). Figure 2 The busbars (2) are arranged parallel to each other, equally spaced and orthogonal to the array of finger lines (3). The interconnection ribbons (5) are welded to the surface of the busbars and help to transfer the current from the connected silicon solar cell onward to another silicon solar cell, a battery or a solar inverter.

[0005] The busbars (2) and finger lines (3) conventionally comprise either high temperature fired pastes or low temperature non-fired pastes - for heat sensitive solar cells such as heterojunction (HJT or HIT) or tandem (perovskite based) solar cells - and are usually achieved by a one or two stage printing process which lays down these metal contacts on and along the solar cell: the use of two consecutive printing stages facilitates the use of different materials for the busbars and finger lines respectively, and also reflects the need to print the busbars at a thinner width than the finger lines. When printing the front side grid in two consecutive stages, typically the finger lines (3) are printed and dried first, and the busbars (2) are printed over the finger lines. While a single printing step will result in similar heights for the busbars and finger lines, in two stage printing an overlap between the two patterns is required in order to have a guaranteed contact between the finger lines and the busbars, and due to possible missalignment between the two patterns. In the overlapping area of ​​the finger lines and bus bars, the height will be different than in the area where only the finger lines or bus bars are printed.

[0006] When the strips (5) are connected to the busbars (2) by a welding process, these strips (5) are thus arranged above the busbars and - in the case of being arranged in front of the solar cells - result in shadow areas extending over the solar cells: this shadow, together with the surface area of ​​the solar cells actually covered by the busbars themselves, leads to a reduction in the efficiency of the photovoltaic module.

[0007] Other problems associated with such solar cell structures include: resistive losses resulting from the high currents passing through the small cross-section ribbon (5); differential thermal contraction of the ribbon (5) and the silicon wafer, which can lead to high stresses in the metallization and silicon; and stresses and microcracks in the silicon wafer caused by the local effects of heat and pressure during the welding process, which hinders the development of thinner wafers.

[0008] Due to these problems, new solar module concepts have been developed, which utilize new interconnection technologies and new solar cell types: for example, one can note multi-wire interconnections on busbarless cells and conductive backsheet interconnections with back-contact cells. However, the present invention is more particularly concerned with the use of conductive adhesives instead of welding and with cell module structures connected in series, especially with shingled cell module structures.

[0009] exist Figure 3In the illustrated shingled cell module structure, solar strips are presented that are rectangular or roughly rectangular in shape. The length of the long side is generally equivalent to the side length of a standard solar wafer (historically 156 mm, but currently increasing in size, even up to 210 mm), while the length of the short side is only a few centimeters. Such solar cell strips have been cut or diced from a standard size processing device (for example, but not limited to, a 156 mm×156 mm device), and appropriate care should be taken during the cutting or dicing process to avoid cracks and similar structural failures. The cells have bus bars or rows of interconnect pads along the long edges, one at the front and one at the back. To create a cell string, interconnect material is applied to connect the rear bus bar of the cell to the front bus bar of the next cell. The cells overlap each other slightly so that the front bus bar is covered by the edge area of ​​the adjacent cell, just like tiles on a roof. Assuming that: i) there is no spacing between cells compared to conventional modules; ii) the cell area shaded by the front bus bar is covered by the active area of ​​another cell; and iii) there are no strips covering the front surface of the cell to cause shading, then this shingled structure results in a module with an extremely high ratio of active area to total area, allowing in principle very high module efficiency.

[0010] Adjacent cells in a given string are bonded to each other at the overlapping portions of the solar cells with a conductive material (4), which can be deposited in different patterns. The use of an electrically conductive adhesive (ECA) as a material for bonding the solar cells together has the advantage that the adhesive overcomes the mechanical stresses that build up due to the mismatch in the coefficient of thermal expansion (CTE) between the different materials used in the photovoltaic module.

[0011] Conductive adhesives (ECAs) are highly filled materials, which are usually characterized by having at least 40% by weight and most often greater than 60% by weight or even 80% by weight of conductive filler particles, which are required to ensure multiple percolation paths and provide good conductivity and low contact resistance. Unfortunately, conductive filler particles do not provide reinforcing properties nor contribute to material cohesion. As a result, the inherent mechanical strength of conductive adhesives is much worse than the same material without fillers.

[0012] It is recognized that photovoltaic modules are subject to temperature variations and high mechanical stresses throughout their life cycle. While these factors have a negative impact on the lifetime of photovoltaic modules, they also place demands on the thermomechanical properties of the conductive adhesive used to bond the constituent solar and / or photovoltaic cells together: the adhesive should overcome the mechanical stresses that build up due to the mismatch in the coefficients of thermal expansion (CTE) between the different materials used in the photovoltaic module; and the polymer matrix of the adhesive should ideally not pass through its glass transition temperature (Tg) within the operating range of the module so as to render it in a glassy, ​​brittle state at strongly negative temperatures (below -10°C).

[0013] In addition to the properties of the cured adhesive obtained, the curing profile of the adhesive is also very important. It is important that: the shelf life of the adhesive at room temperature is feasible; the curing time is feasible at a temperature that does not adversely affect the electronic components and metallization features; faster curing speeds combined with lower curing temperatures enable high throughput in the manufacture of assembled components; the adhesive is applicable - preferably dispensable or printable - and curable in industrial production processes for high-volume manufacturing; and the adhesive has negligible oozing out of the component joints.

[0014] The compositions described in the literature are often relatively rigid, or have poor conductivity or low adhesion characteristics. The advantage of thermosetting epoxies is that they can vary between very rigid and very flexible materials, but if the adhesive is too flexible, it is difficult to maintain stable electrical contact with the solar cell, and the adhesive's contact resistance with the solar cell tends to increase during thermal cycling between -40°C and 85°C and / or during aging at 85°C in a high humidity environment (85% humidity). However, typical conductive epoxies require relatively long cure times to develop sufficient adhesion, and they may be too rigid to survive thermal reliability testing.

[0015] Therefore, there is a need for an adhesive composition that provides faster cure speed and lower cure temperature to achieve high throughput in the manufacture of assembled components, while providing flexibility and the ability to absorb mechanical stress to ensure long-term reliability performance of electronic components or devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 a illustrates a basic solar cell configuration with three bus bars (2).

[0017] Figure 1 b illustrates a basic solar cell configuration with four bus bars (2).

[0018] Figure 2 The example shows how the finger wires (3) collect current from the surface of a silicon solar cell and transfer it to the interconnect ribbon (5) via a bus bar.

[0019] Figure 3 The example illustrates a shingled battery module structure. Summary of the invention

[0020] The present invention relates to a conductive composition comprising: a) 5 to 25 wt% of a cycloaliphatic epoxy resin, based on the total weight of the composition; b) 0.05 to 10 wt% of a vinyl ether, based on the total weight of the composition; c) 0.1 to 0.45 wt% of an onium salt, based on the total weight of the composition; d) 0.01 to 10 wt% of a free radical initiator, based on the total weight of the composition; e) 45 to 85 wt% of conductive particles, based on the total weight of the composition; and f) 0.1 to 10 wt% of an organic solvent, based on the total weight of the composition.

[0021] The present invention also includes a cured product of the conductive composition according to the present invention.

[0022] The present invention relates to the use of the conductive composition according to the invention as an adhesive in electronic applications, preferably as an adhesive in shingled module photovoltaic applications.

[0023] The present invention also relates to a photovoltaic module comprising: a series connected string of two or more solar cells in a shingled pattern with conductive bonds between the two or more solar cells, wherein the conductive bonds are formed with the conductive composition or with the cured product according to the present invention. DETAILED DESCRIPTION

[0024] In the following paragraphs, the present invention will be described in more detail. Unless there is a clear contrary indication, each aspect described can be combined with any one or more other aspects. In particular, any feature indicated as preferred or advantageous can be combined with any one or more other features indicated as preferred or advantageous.

[0025] In the context of the present invention, unless the context requires otherwise, the terms used are to be interpreted according to the following definitions.

[0026] As used herein, the singular forms "a," "an," and "the" include singular and plural referents unless the context clearly dictates otherwise.

[0027] As used herein, the terms "comprising" and "containing" are synonymous with "including" or "containing", are inclusive or open-ended, and do not exclude additional, unrecited members, elements, or method steps.

[0028] As used herein, the term "consisting of" excludes any elements, ingredients, members, or method steps not specified.

[0029] "Preferred", "preferably", "desirably" and "particularly" are often used herein to refer to embodiments of the present disclosure that may provide specific benefits in certain circumstances. However, the listing of one or more preferred, preferred, desired or particular embodiments does not mean that other embodiments are not useful, and is not intended to exclude these other embodiments from the scope of the present disclosure.

[0030] As used throughout this application, the words "may" or "may" are used in a permissive sense (ie, meaning having the potential to), rather than in a mandatory sense.

[0031] Recitations of numerical endpoints include all numbers and fractions within the corresponding range, as well as the recited endpoints.

[0032] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned herein are based on weight.

[0033] When an amount, concentration or other value or parameter is expressed in the form of a range, a preferred range or a preferred upper value and a preferred lower value, it should be understood that any range obtained by combining any upper limit or preferred upper value with any lower limit or preferred lower value is specifically disclosed, regardless of whether the obtained range is explicitly mentioned in the context.

[0034] As used herein, the term "one-component (1K) composition" refers to a composition in which the components of the composition are mixed together during storage of the composition, but the properties of the composition (including viscosity) remain sufficiently consistent during the storage time to allow successful subsequent use of the composition.

[0035] A "two-component (2K) composition" is understood to be a composition in which the first component / part and the second component / part have to be stored in separate containers due to their (high) reactivity. The two components / parts are mixed only shortly before application and then react, usually without additional activation, forming bonds and thus a polymer network. Here, higher temperatures can be applied to accelerate the crosslinking reaction.

[0036] As used herein, the term "fast cure" refers to a fast curing time, which is generally 10 to 60 seconds at about 120 to 200°C.

[0037] The entire contents of all references cited in this specification are incorporated herein by reference.

[0038] Unless otherwise defined, all terms (including technical and scientific terms) used in disclosing the present invention have the meaning commonly understood by one of ordinary skill in the art to which the present invention belongs. By way of further guidance, term definitions are included to better understand the teachings of the present invention.

[0039] The present invention relates to a conductive composition comprising: a) 5 to 25 wt% of a cycloaliphatic epoxy resin, based on the total weight of the composition; b) 0.05 to 10 wt% of a vinyl ether, based on the total weight of the composition; c) 0.1 to 0.45 wt% of an onium salt, based on the total weight of the composition; d) 0.01 to 10 wt% of a free radical initiator, based on the total weight of the composition; e) 45 to 85 wt% of conductive particles, based on the total weight of the composition; and f) 0.1 to 10 wt% of an organic solvent, based on the total weight of the composition.

[0040] The composition according to the present invention is a fast-curing conductive epoxy adhesive having low contact resistance with the metallization of silicon solar cells, low volume resistivity, high flexibility and high adhesion to the metallization of silicon solar cells.

[0041] The conductive composition according to the present invention comprises a cycloaliphatic epoxy resin. The cycloaliphatic epoxy resin is used because the resin comprising one cyclohexyl oxide ring cures faster than aromatic epoxy resins or aliphatic epoxy resins.

[0042] Suitable cycloaliphatic epoxy resins contain at least one cyclohexyl oxide ring and are preferably selected from bis(7-oxabicyclo[4.1.0]hept-3-ylmethyl)adipate, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexylcarboxylate, 7-oxabicyclo[4.1.0]hept-3-yl methacrylate, 3,4-epoxycyclohexanecarboxylic acid methyl ester, bis(oxiran-2-ylmethyl)cyclohexane-1,2-dicarboxylate and mixtures thereof, preferably selected from bis(7-oxabicyclo[4.1.0]hept-3-ylmethyl)adipate, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexylcarboxylate and mixtures thereof.

[0043] The cycloaliphatic epoxy resins listed above are preferred because of their fast curing characteristics.

[0044] Commercially available cycloaliphatic epoxy resins suitable for use in the present invention include, but are not limited to, Celloxide 2021P from Daicel Corporation and Celloxide 2021P from IGM Resin Corporation. s Omnilan e OC 3005.

[0045] The conductive composition according to the present invention comprises 5 to 25 wt %, preferably 8 to 20 wt %, and more preferably 11 to 19 wt % of the cycloaliphatic epoxy resin based on the total weight of the composition.

[0046] The above range is preferred because less than 5% of the cycloaliphatic epoxy resin may mean a lack of binder in the composition, while more than 25% may result in a polymer that is too rigid.

[0047] The conductive composition according to the present invention comprises vinyl ether. Vinyl ether is desirable in the composition because it enables fast curing to be obtained at low temperatures.

[0048] Preferably the vinyl ether is an aliphatic vinyl ether, more preferably selected from 4-hydroxybutyl vinyl ether, diethylene glycol divinyl ether, cyclohexane-dimethanol divinyl ether, dodecyl vinyl ether, cyclohexyl divinyl ether, 2-ethylhexyl vinyl ether, dipropylene glycol divinyl ether, hexanediol divinyl ether, octadecyl vinyl ether, butanediol divinyl ether, triethylene glycol divinyl ether and mixtures thereof, preferably selected from 4-hydroxybutyl vinyl ether, diethylene glycol divinyl ether and mixtures thereof.

[0049] The above vinyl ethers are preferred because they are electron-rich vinyl ethers and they react quickly with free radicals.

[0050] Commercially available vinyl ethers suitable for use in the present invention include, but are not limited to, 4-hydroxybutyl vinyl ether and diethylene glycol divinyl ether from BASF.

[0051] The vinyl ether is present in an amount of 0.05 to 10 wt%, preferably 0.1 to 5 wt%, and more preferably 0.25 to 2 wt%, based on the total weight of the composition.

[0052] The above range is preferred because less than 0.05% of vinyl ether may not cure quickly at low temperatures, while more than 10% may cause outgassing.

[0053] The conductive composition according to the present invention comprises an onium salt. Onium salts are preferred because free radical addition intermediates react in a preferred manner with onium salts compared to other photoinitiators.

[0054] Onium salts suitable for use in the present invention include iodonium salts, sulfonium salts, diazonium salts, ammonium salts or mixtures of those salts.

[0055] In one embodiment, the onium salt is an iodonium salt of the formula

[0056] R——I + —RX-

[0057] wherein R is independently selected from phenyl, halogenated phenyl (e.g., chlorophenyl) and C1-C20 alkylphenyl (e.g., dodecylphenyl), and X is any suitable counter anion, such as a halogen anion, CF3SO3 - 、C6H5SO3 - 、NO3- 、AsF6 - 、SbF6 - 、FeCl4 - 、SbCl6 - 、BF4 - PF6 - , and (C6F5)B - .

[0058] Preferably, the onium salt is selected from cumyltolyliodonium tetrakis(pentafluorophenyl)borate, [4-(acetoxy)phenyl]methyl(phenylmethyl)sulfonium hexafluorophosphate, (4-hydroxyphenylmethyl(1-naphthylmethyl))sulfonium hexafluorophosphate, 4-(acetoxyphenyl)benzyl(methyl)sulfonium, tetrakis(pentafluorophenyl)borate and mixtures thereof, more preferably the onium salt is cumyltolyliodonium tetrakis(pentafluorophenyl)borate.

[0059] The above onium salts are preferred because they cure faster with free radical addition intermediates compared to other photoinitiators.

[0060] Commercially available onium salts suitable for use in the present invention include, but are not limited to, Bluesil PI 2074 from Elkem.

[0061] The composition according to the invention comprises from 0.1 to 0.45% by weight, preferably from 0.15 to 0.4% by weight and more preferably from 0.15 to 0.3% by weight of onium salt, relative to the total weight of the composition.

[0062] The above range is preferred because less than 0.1% of the onium salt may cause the reaction to not proceed, while more than 0.45% may not provide any further advantage but increase the cost.

[0063] The conductive composition according to the present invention comprises a free radical initiator. The free radical initiator suitable for use in the present invention is a peroxide, preferably an organic peroxide.

[0064] In one embodiment of the present invention, the free radical initiator comprises or consists of at least one peroxide compound represented by the following formula:

[0065] R

[0066] wherein: Rp is an aliphatic or aromatic group containing no more than 18 carbon atoms, and Rq is H or an aliphatic or aromatic group containing no more than 18 carbon atoms; and preferably, wherein: Rp and Rq are C1 to C12 alkyl, C6 to C18 aryl or C7 to C18 aralkyl.

[0067] Preferably, the free radical initiator is selected from the group consisting of cumene hydroperoxide (CHP), p-menthane hydroperoxide, tert-butyl hydroperoxide (TBH), tert-butyl perbenzoate, tert-butyl peroxyvalerate, di-tert-butyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxy-2-hexanoate, tert-amyl hydroperoxide, 1,2,3,4-tetramethylbutyl hydroperoxide, benzoyl peroxide, dibenzoyl peroxide, 1,3-bis(tert-butylperoxyisopropyl)benzene, diacetyl peroxide, 4,4 -butyl di(tert-butylperoxy)valerate, p-chlorobenzoyl peroxide, tert-butyl isopropyl peroxide, di-tert-butyl peroxide, dicumyl peroxide, didodecanoyl peroxide, 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2,5-dimethyl-2,5-di-tert-butylperoxyhex-3-yne, and 4-methyl-2,2-di-tert-butylperoxypentane, tert-butyl peroxyneodecanoate and mixtures thereof; preferably the free radical initiator is tert-butyl peroxyneodecanoate.

[0068] These preferred free radical initiators based on peroxide compounds provide a desirable balance between profile, cure speed, adhesion and electrical properties.

[0069] Commercially available free radical initiators suitable for use in the present invention include, but are not limited to, Luperox DCP, Luperox P, and Luperox 10 from Arkema.

[0070] The composition according to the invention comprises from 0.01 to 10% by weight, preferably from 0.02 to 5% by weight and more preferably from 0.05 to 2.0% by weight of free-radical initiator, relative to the total weight of the composition.

[0071] The above range is preferred because less than 0.01% of the free radical initiator may result in poor curing properties, while more than 10% may result in poor shelf life.

[0072] The conductive composition according to the present invention comprises conductive particles.

[0073] The conductive particles can be needle-shaped, spherical, ellipsoidal, cylindrical, bead-shaped, cubic or flake-shaped, and they can be used alone or in combination. The conductive particles can be, for example, a mixture of spherical particles and flake-shaped particles. In addition, it is contemplated that agglomerates of more than one particle type can be used.

[0074] The average volumetric particle size of the conductive particles, as measured by a laser diffraction / scattering method, is generally from 300 nm to 50 μm, for example from 500 nm to 40 μm, more preferably from 500 nm to 30 μm.

[0075] In a highly preferred embodiment, the conductive particles have a D10 of about 10 μm, a D50 of about 5 μm, and a D90m of about 12 μm.

[0076] In the above-mentioned measurement method, the particle size is measured by a particle size analyzer, and the particle shape is analyzed by a scanning electron microscope. In short, the scattered laser light from the particles is detected by a detector array. Theoretical calculations are performed to fit the measured scattered light intensity distribution. During the fitting process, the particle size distribution is derived, and in particular the D10, D50 and D90 values ​​are calculated accordingly.

[0077] The particle size is measured by using a particle size distribution (PSD) method. In the present invention, the average particle size is measured by laser diffraction, preferably using a Malvern Mastersizer 2000 or a Malvern Mastersizer 3000 available from Malvern Instruments Ltd. or a Horiba LA-950V2 available from Horiba Ltd. In this technique, the size of the particles in the suspension or emulsion is measured by diffraction using a laser beam based on the application of Fraunhofer or Mie theory. In the present invention, Mie theory or modified Mie theory is applied to non-spherical particles, and the particle size is related to scattering measurements at an angle of 0.02 to 135 degrees relative to the incident laser beam.

[0078] For assurance, it is noted that conductive particles suitable for use in the present invention may be a mixture of particles having a small particle size and particles having a larger particle size.

[0079] In the independent characterization of the particles (which may or may not conform to the above particle size distribution), it is preferred to use a 25 cm 3 The tap density of the conductive particles measured by a graduated glass cylinder is 0.5 g / cm 3 Up to 6.0g / cm 3 , preferably 0.5g / cm 3 Up to 5.5g / cm 3 , more preferably 0.5 g / cm 3 Up to 5.0g / cm 3 The principle of the specified method is to tap a specified amount of powder in a container with the aid of a tapping device until the volume of the powder no longer decreases. The mass of the powder after the test is divided by its volume to give its tap density.

[0080] In an independent characterization of the particles (which may or may not conform to the above particle size distribution), it is preferred that the specific surface area of ​​the conductive particles is from 0.3 to 2 m 2 / g, preferably 0.5 to 1.5 m 2 / g, more preferably 0.75 to 1.3 m 2 The term "specific surface area" used herein refers to the BET specific surface area determined according to ASTM B922-10 using nitrogen as an analytical gas.

[0081] Preferably, the conductive particles are selected from silver, nickel, carbon, carbon black, graphite, graphene, copper, gold, platinum, aluminum, iron, zinc, cobalt, lead, tin alloys, silver-coated nickel, silver-coated copper, silver-coated graphite, silver-coated polymers, silver-coated aluminum, silver-coated glass, silver-coated carbon, silver-coated boron nitride, silver-coated aluminum oxide, silver-coated aluminum hydroxide, nickel-coated graphite, and mixtures thereof; preferably, the conductive particles are selected from silver, carbon black, graphite, graphene, copper, silver-coated nickel, silver-coated copper, silver-coated graphite, silver-coated polymers, silver-coated aluminum, silver-coated glass, silver-coated carbon, silver-coated boron nitride, silver-coated aluminum oxide, silver-coated aluminum hydroxide, nickel-coated graphite, and mixtures thereof; more preferably, the conductive particles are selected from silver, silver-coated copper, silver-coated graphite, silver-coated polymers, and mixtures thereof.

[0082] Commercially available conductive particles suitable for use in the present invention include, but are not limited to, SF91, SF 98, and SF102 from Ames Goldsmith and EA-SA-0200 and SA-0201 from Metalor.

[0083] The composition according to the invention comprises 45 to 85 wt %, preferably 63 to 78 wt % and more preferably 68 to 75 wt % of conductive particles, relative to the total weight of the composition.

[0084] The above range is preferred because less than 45% of the conductive particles may result in too high a resistivity, while more than 85% may result in the adhesive becoming brittle and costly.

[0085] The conductive composition according to the present invention contains an organic solvent. The organic solvent is used to dissolve the onium salt.

[0086] Preferably, the organic solvent is a polar aprotic solvent or a protic solvent or a mixture thereof, more preferably selected from acetone, ethyl acetate, dimethylformamide, acetonitrile, dimethyl sulfoxide, butyl lactate, propylene carbonate, a polymer of 2-oxacycloheptanone and 2,2-dimethyl-1,3-propanediol, polycaprolactone diol and a mixture thereof.

[0087] Commercially available solvents suitable for use in the present invention include, but are not limited to, Capromer PD1-10 and Capromer PD1-20 from BASF; Placcel 205UT, Placcel 205H, and Placcel 210 from Daicel; and propylene carbonate from Sinopharm.

[0088] The composition according to the invention comprises from 0.1 to 10% by weight, preferably from 0.15 to 5% by weight and more preferably from 0.2 to 2% by weight of organic solvent, relative to the total weight of the composition.

[0089] The above range is preferred because less than 0.1% of the solvent may dissolve all of the onium salt, leaving lumps in the composition, while more than 10% may cause degassing.

[0090] The conductive composition according to the present invention may further comprise a thermosetting modifier resin. Thermosetting modifier resins are preferred because they provide flexibility (not too hard) to the final polymer. If the final polymer is too hard, the composition may not pass the mechanical load test, which is particularly desirable in solar applications.

[0091] Thermosetting modifier resins suitable for use in the present invention are epoxy resins, oxetane resins, (meth)acrylate resins, silicone resins and mixtures thereof. It is worth noting that suitable thermosetting modifier resins, when present and when they are epoxy resins, are different from the cycloaliphatic epoxy resins described above.

[0092] The thermosetting modifier resin can be selected from aliphatic epoxy resins, epoxy phenolic resins, bisphenol-A-epoxy resins, bisphenol-F-epoxy resins, hydrogenated bisphenol-A-epoxy resins, hydrogenated bisphenol-F-epoxy resins, bisphenol-A epichlorohydrin-based epoxy resins, propylene glycol epoxy resins, reaction products of polyether-polyols with epichlorohydrin, polycarbonate diol-based glycidyl ethers, epichlorohydrin formaldehyde phenolic resins, epichlorohydrin phenol phenolic resins, epichlorohydrin o-cresol phenolic resins, epichlorohydrin m-xylene diamine resins, epichlorohydrin diaminodiphenylmethane resins, epichlorohydrin trimethylolpropane resins, epoxy silicone copolymers, and mixtures thereof.

[0093] In a preferred embodiment, the thermosetting modifier resin is selected from 1,6-hexanediol diacrylate, 3-ethyl-3-[((2-ethylhexyl)-oxy)methyl]oxetane, bis[1-ethyl(3-oxetanyl)]methyl ether, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,3-bis(glycidylpropyl)tetramethyldisiloxane, glycidoxypropyl terminated polydimethylsiloxane (8-11), 1,3-bis[2-(3,4-epoxycyclohexyl)ethyl]tetramethyldisiloxane, and mixtures thereof.

[0094] Thermoset modifier resins listed above are preferred because they produce lower Tg and more flexible materials, which are advantageous in shingled module photovoltaic applications.

[0095] Commercially available thermosetting modifier resins suitable for use in the present invention include, but are not limited to: 7200, Epiclon EXA-4850 available from DIC, SIB1115.0 from Gelest, Capa 2201A from Ingevity, and Resin 825.

[0096] The thermosetting modifier resin may be present in an amount of 0.2 to 9.5 wt %, preferably 1 to 8 wt %, and more preferably 1 to 7 wt %, based on the total weight of the composition.

[0097] The above range is preferred because less than 0.2% of the thermosetting modifier resin may negatively affect the composition by reducing the cure speed and increasing the volume resistivity, while more than 9.5% may negatively affect the mechanical bending test performance.

[0098] The conductive composition according to the present invention may further comprise a toughening agent. A toughening agent is preferred in the composition because it can help to avoid stress propagation, especially during mechanical loading tests.

[0099] Toughening agents suitable for use in the present invention may be epoxy-elastomer adducts and / or toughened rubbers in the form of core-shell rubber particles.

[0100] The term "core-shell rubber" or CSR is used according to its standard meaning in the art and refers to a rubber particle core formed by a polymer comprising an elastomer or rubbery polymer as a major component and a shell formed by a polymer graft polymerized onto the core. During the graft polymerization process, the shell partially or completely covers the surface of the rubber particle core. By weight, the core should account for at least 50% by weight of the core-shell rubber particle.

[0101] The polymer material of the core should have a glass transition temperature (Tg) not higher than 0°C, and preferably a glass transition temperature (Tg) of -20°C or lower, more preferably -40°C or lower, even more preferably -60°C or lower. The polymer of the shell is a non-elastomeric, thermoplastic or thermosetting polymer having a glass transition temperature (Tg) higher than room temperature, preferably higher than 30°C, more preferably higher than 50°C.

[0102] The core may include: diene homopolymers, such as homopolymers of butadiene or isoprene; diene copolymers, such as copolymers of butadiene or isoprene with one or more ethylenically unsaturated monomers (such as vinyl aromatic monomers, (meth)acrylonitrile or (meth)acrylates); polymers based on (meth)acrylate monomers, such as polybutyl acrylate; and polysiloxane elastomers, such as polydimethylsiloxane and cross-linked polydimethylsiloxane.

[0103] Similarly, the shell may comprise a polymer or copolymer of one or more monomers selected from: (meth)acrylates, such as methyl methacrylate; vinyl aromatic monomers, such as styrene; vinyl cyanides, such as acrylonitrile; unsaturated acids and anhydrides, such as acrylic acid; and (meth)acrylamide. The polymer or copolymer used in the shell may have acid groups that are ionically crosslinked by metal carboxylate formation, in particular by forming salts of divalent metal cations. The shell polymer or copolymer may also be covalently crosslinked by monomers having two or more double bonds per molecule.

[0104] Preferably, any included core-shell rubber particles have an average particle size (d50) of from 10 nm to 300 nm, such as from 50 nm to 250 nm: the particle size refers to the diameter or maximum dimension of the particle in the particle distribution and is measured by dynamic light scattering. For completeness, the present application does not exclude the presence of two or more types of core-shell rubber (CSR) particles having different particle size distributions in the composition to provide a balance of key properties of the resulting cured product, including shear strength, peel strength and resin fracture toughness.

[0105] The core-shell rubber may be selected from commercially available products, examples of which include, but are not limited to: Paraloid EXL 2650A, EXL 2655 and EXL 2691 A available from Dow Chemical Company; XT100; available from Kaneka Corporation MX series, specifically MX 120, MX125, MX 130, MX 136, MX 551, MX553; and METABLEN SX-006 available from Mitsubishi Rayon.

[0106] The toughening agent may be present in an amount of 1 to 10 wt %, preferably 1.5 to 9 wt %, and more preferably 2 to 8 wt %, based on the total weight of the composition.

[0107] The above range is preferred because less than 1% of toughening agent may not bring any technical advantage, while more than 10% may cause the viscosity of the composition to increase too much.

[0108] The conductive composition according to the present invention may further comprise an adhesion promoter. An adhesion promoter may be added to the composition to improve the adhesion of the epoxy resin to the substrate. The adhesion promoter may work by forming a new layer at the interface that is strongly bonded to both the substrate and the adhesive composition. The resulting interface region may also be more resistant to chemical attack from the environment.

[0109] The choice of adhesion promoter may be determined by the type of surface to which the composition is to be applied. That is, the most common commercially available adhesion promoters are organosilanes, certain types of which are epoxy-functional organosilanes are mentioned above.

[0110] Adhesion promoters suitable for use in the present invention are, for example, silane compounds such as mercaptopropyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane and 3-acryloxypropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, bis-(γ-trimethoxysilylpropyl)amine, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, tris-(γ-trimethoxysilyl)isocyanurate and mixtures thereof.

[0111] Commercially available adhesion promoters suitable for use in the present invention include, but are not limited to, Silquest A-187 from Momentive.

[0112] The adhesion promoter may be present in an amount of 0.01 to 10 wt %, preferably 1.5 to 9 wt %, and more preferably 2 to 8 wt %, based on the total weight of the composition.

[0113] If the amount of the adhesion promoter is less than 0.01%, it may not provide a desired adhesive strength. On the other hand, an amount greater than 10% may not improve the adhesive strength but simply saturate the composition.

[0114] The conductive composition according to the present invention may further comprise a free radical inhibitor. The free radical inhibitor in the composition can scavenge and stabilize free radicals that may come from premature decomposition of peroxide.

[0115] In a highly preferred embodiment, a free radical inhibitor is present in the composition.

[0116] The free radical inhibitor can be selected from butylated hydroxytoluene, 4-hydroxyphenyldimethylsulfonium methyl sulfate, 2-tert-butyl-1,4-benzoquinone, tert-butylhydroquinone, 1,4-benzoquinone, hydroquinone, 4-methoxyphenol, phenothiazine, 6-tert-butyl-2,4-dimethylphenol, 2,6-di-tert-butylphenol, 2,6-di-tert-butyl-p-cresol and mixtures thereof; preferably, the free radical inhibitor is butylated hydroxytoluene.

[0117] Commercially available free radical inhibitors suitable for use in the present invention include, but are not limited to, butylated hydroxytoluene from TCI Chemicals.

[0118] The free radical inhibitor may be present in an amount of 0.01 to 0.05 wt%, preferably 0.02 to 0.04 wt%, based on the total weight of the composition.

[0119] The above range is preferred because less than 0.01% of the free radical inhibitor may result in a shorter shelf life, while more than 0.05% may negatively affect the curing speed.

[0120] The conductive composition according to the present invention preferably has a -1 The conductive composition according to the present invention preferably has a thinning index (TI) of 1.2 to 6, wherein the TI is measured according to the test method listed in the following Examples section.

[0121] The conductive composition according to the present invention preferably has a die shear strength of 2 to 20 kg, preferably 4 to 15 kg, wherein the die shear strength is measured according to the test method listed in the Examples section below.

[0122] The conductive composition according to the present invention preferably has a manual bending test result of 50 to 100%, preferably 75 to 100%, wherein the manual bending force is measured according to the test method listed in the Examples section below.

[0123] The present invention relates to a cured product of the conductive composition according to the present invention. The composition can be rapidly cured at a temperature of 120 to 200° C. within 10 to 60 seconds.

[0124] The conductive composition according to the present invention can be used as an adhesive in electronic applications, preferably as an adhesive in shingled module photovoltaic applications.

[0125] The present invention also relates to a photovoltaic module comprising: a series-connected string of two or more solar cells in a shingled pattern with conductive bonds between the two or more solar cells, wherein the conductive bonds are formed with the conductive composition according to the present invention or a cured product of the conductive composition.

[0126] When producing photovoltaic modules, the conductive composition according to the invention is applied by dispensing, spraying or printing.

[0127] Example

[0128] Test Methods—The following test methods were used to measure the physical properties of the examples:

[0129] Viscosity at 1.5 (AR-crs-p2cm / 200μm) according to method ISO 3219

[0130] Viscosity at 15 (AR-csr-p2cm-200μm) according to method ISO 3219

[0131] VR 15 min 150°C (box oven) according to method ASTM D 2739-72 (a 5.4 cm x 5 mm x 60 micron adhesive track was printed onto a glass slide and cured in a box oven at 150°C for 15 minutes.)

[0132] VR 90s 180°C (hot plate) According to method ASTM D 2739-72 (A 5.4 cm x 5 mm x 60 micron adhesive track was printed onto a glass slide and cured at 180°C on a hot plate for 90 s.)

[0133] VR 60s 160°C (hot plate) According to method ASTM D 2739-72 (A 5.4 cm x 5 mm x 60 micron adhesive track was printed onto a glass slide and cured at 160°C on a hot plate for 60 s.)

[0134] Die shear strength

[0135] Two Kapton tape lines are attached to the ceramic plate, leaving a spacing of 2 mm between them. A second layer of tape is applied on each line. The adhesive is then scraped between the two tapes with a scraper and scraped with the aid of a glass slide to a wet thickness of about 70 to 90 microns. The Kapton tape is then removed, and a 2x2 mm chip is placed on the adhesive track, applying gentle uniform pressure. The plate is cured with the desired curve (60s 160°C on a heating plate (DSS 60s 160°C HP), 90s 160°C (DSS 90s 160°C HP) or 90s180°C DSS 90s 180°C HP), and after cooling down for 1 to 2h, the chip can be sheared with a Dage chip shear tester. The chip shear strength is then reported in kg.

[0136] Manual bend test

[0137] An adhesive pattern consisting of 10 or 15 500 x 4000 micron pads was printed on the front busbar of the shingled cell by template. The second shingle was manually assembled on top so that the adhesive connected the front busbar of the bottom shingle to the rear busbar of the top shingle. This 2-shingle assembly was then cured on a hot plate with the desired curing profile (60s 160°C hot plate, 90s 160°C hot plate, or 90s 180°C hot plate). After curing, the assembly was cooled for 5 minutes and the two shingles were manually separated by applying a bending force by hand. The qualitative adhesion is proportional to the number of pads showing cell breakage: very high adhesion (VHA) corresponds to 100% of the pads showing cell breakage, high adhesion (HA) corresponds to 75% of the pads showing cell breakage, medium adhesion (MA) corresponds to 50% of the pads showing cell breakage, and low adhesion (LA) corresponds to <= 25% of the pads showing cell breakage. No adhesion (NA) corresponds to 0% cell failure.

[0138] The following examples were prepared by mixing all ingredients together.

[0139] Table 1 below lists Comparative Examples 1 to 3. These examples were prepared to study the effects of free radical initiator, vinyl ether and epoxy resin on the composition.

[0140] Table 1

[0141]

[0142]

[0143] Examples 4 and 5 are shown below in Table 2. These examples were prepared to study the effect of thermosetting resin modifiers on the compositions.

[0144] Table 2

[0145]

[0146] Table 1 shows the effect of vinyl ether, free radical initiator and epoxy resin on manual bend test adhesion. Only when the peroxide free radical initiator was present with diethylene glycol divinyl ether and combined with the correct resin modifier was any adhesion achieved (Example 5). When comparing Example 3 with the examples in Table 2, the importance of using a high percentage of cycloaliphatic epoxy resin compared to a standard epoxy resin can be seen. Comparative Examples 1 to 3 illustrate that, independent of any divinyl ether or free radical initiator combination, no adhesion was achieved and incomplete or no cure was observed.

[0147] Table 3 below lists the components of Examples 6 and 7. These examples were prepared to study the effect of the thermosetting modifier resin on the compositions.

[0148] Table 3

[0149]

[0150] Examples 5 and 6 in Table 3 demonstrate the importance of having a high percentage of cycloaliphatic epoxy resin in the formulation for rapid adhesion in the manual bend test. Example 5 contains a higher percentage of Omnilane OC 3005 and KaneAce MX toughener (core-shell rubber particles dispersed in 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate), while Example 6 contains UviCure S150 (a difunctional oxetane) instead. Example 5 produces lower adhesion even with a short and low temperature cure curve, and produces very high adhesion with an extended and higher cure temperature cure curve. This indicates that the increase in the percentage of cycloaliphatic in the formulation either increases the cure speed, or improves the bending performance, or a combination of the two. It is also worth noting that Examples 5 and 6 show higher volume resistivity compared to the examples given in Table 1.

[0151] Table 4 below lists the components of Examples 8 through 13. These examples were prepared to study the effects of conductive particles and thermosetting modifier resin on the compositions.

[0152] Table 4

[0153]

[0154]

[0155] Examples 8 to 13 in Table 4 demonstrate key findings involving the selection of conductive particles to achieve low volume resistivity and the importance of a flexible resin modifier in achieving very high hand bend test adhesion. Comparing Examples 8 and 9, it can be seen that switching to P892-29 conductive particles significantly reduces volume resistivity compared to SF98, even at lower loadings. This demonstrates that conductive particle selection has an impact on performance.

[0156] Comparison of Examples 8 to 13 shows the importance of adding a flexible resin modifier to the base epoxy system. High adhesion is only achieved with the addition of a resin modifier containing a siloxane backbone; presumably this imparts the flexibility that is critical for high adhesion in flexural properties. Specifically, comparison of Examples 10 and 13 shows that very high adhesion can be achieved by simply adding a flexible resin modifier.

[0157] Table 5 below lists the components of Examples 14 through 16. These examples were prepared to study the effect of the thermosetting modifier resin on the compositions.

[0158] Table 5

[0159]

[0160] The examples in Table 5 demonstrate the effect of resin modifiers on manual bend test adhesion performance. Comparison of the manual bend test results for Examples 14, 15, and 16 shows the effect of resin modifier function and loading. In Example 16, SIB115.0 was used only at relatively high loads and resulted in no adhesion in the manual bend test. In contrast, in Examples 14 and 16, extremely high adhesion was achieved in the manual bend test by using lower loads of SIB115.0 and adding a second resin modifier (Epalloy 7200 and Capa 2201A, respectively). These examples emphasize that the optimal ratio of resin / modifier results in the best adhesion.

Claims

1. A conductive composition comprising: a) 5 to 25 wt % of a cycloaliphatic epoxy resin, based on the total weight of the composition; b) 0.05 to 10% by weight of vinyl ether, based on the total weight of the composition; c) 0.1 to 0.45 wt % of an onium salt, based on the total weight of the composition; d) 0.01 to 10 wt % of a free radical initiator, based on the total weight of the composition; e) 45 to 85 wt % of conductive particles, based on the total weight of the composition; and f) 0.1 to 10 wt % of an organic solvent, based on the total weight of the composition.

2. The conductive composition according to claim 1, wherein the alicyclic epoxy resin contains at least one cyclohexyl oxide ring and is preferably selected from bis(7-oxabicyclo[4.1.0]hept-3-ylmethyl)adipate, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexylcarboxylate, 7-oxabicyclo[4.1.0]hept-3-yl methacrylate, 3,4-epoxycyclohexanecarboxylic acid methyl ester, bis(oxiran-2-ylmethyl)cyclohexane-1,2-dicarboxylate and mixtures thereof, preferably selected from bis(7-oxabicyclo[4.1.0]hept-3-ylmethyl)adipate, (3',4'-epoxycyclohexane)methyl 3,4-epoxycyclohexylcarboxylate and mixtures thereof.

3. The conductive composition according to claim 1 or 2, wherein the cycloaliphatic epoxy resin is present in an amount of 8 to 20 wt%, preferably 11 to 19 wt%, based on the total weight of the composition.

4. The conductive composition according to any one of claims 1 to 3, wherein the vinyl ether is selected from 4-hydroxybutyl vinyl ether, diethylene glycol divinyl ether, cyclohexane-dimethanol divinyl ether, dodecyl vinyl ether, cyclohexyl divinyl ether, 2-ethylhexyl vinyl ether, dipropylene glycol divinyl ether, hexanediol divinyl ether, octadecyl vinyl ether, butanediol divinyl ether, triethylene glycol divinyl ether and mixtures thereof, preferably selected from 4-hydroxybutyl vinyl ether, diethylene glycol divinyl ether and mixtures thereof.

5. The conductive composition according to any one of claims 1 to 4, wherein the vinyl ether is present in an amount of 0.1 to 5 wt%, preferably 0.25 to 2 wt%, based on the total weight of the composition.

6. The conductive composition according to any one of claims 1 to 5, wherein the onium salt is selected from cumyltolyliodonium tetrakis(pentafluorophenyl)borate, [4-(acetoxy)phenyl]methyl(phenylmethyl)sulfonium hexafluorophosphate, (4-hydroxyphenylmethyl(1-naphthylmethyl))sulfonium hexafluorophosphate, 4-(acetoxyphenyl)benzyl(methyl)sulfonium, tetrakis(pentafluorophenyl)borate and mixtures thereof, preferably the onium salt is cumyltolyliodonium tetrakis(pentafluorophenyl)borate.

7. The conductive composition according to any one of claims 1 to 6, wherein the onium salt is present in an amount of 0.15 to 0.4 wt%, preferably 0.15 to 0.3 wt%, based on the total weight of the composition.

8. The conductive composition according to any one of claims 1 to 7, wherein the free radical initiator is present in an amount of 0.02 to 5 wt%, preferably 0.05 to 2.0 wt%, based on the total weight of the composition.

9. The conductive composition according to any one of claims 1 to 8, wherein the conductive particles are selected from silver, nickel, carbon, carbon black, graphite, graphene, copper, gold, platinum, aluminum, iron, zinc, cobalt, lead, tin alloy, silver-coated nickel, silver-coated copper, silver-coated graphite, silver-coated polymer, silver-coated aluminum, silver-coated glass, silver-coated carbon, silver-coated boron nitride, silver-coated aluminum oxide, silver-coated aluminum hydroxide, nickel-coated graphite, and mixtures thereof; preferably the conductive particles are selected from silver, carbon black, graphite, graphene, copper, silver-coated nickel, silver-coated copper, silver-coated graphite, silver-coated polymer, silver-coated aluminum, silver-coated glass, silver-coated carbon, silver-coated boron nitride, silver-coated aluminum oxide, silver-coated aluminum hydroxide, nickel-coated graphite, and mixtures thereof; more preferably the conductive particles are selected from silver, silver-coated copper, silver-coated graphite, silver-coated polymer, and mixtures thereof.

10. The conductive composition according to any one of claims 1 to 9, wherein the conductive particles are present in an amount of 63 to 78 wt%, preferably 68 to 75 wt%, based on the total weight of the composition.

11. The conductive composition according to any one of claims 1 to 10, wherein the organic solvent is a polar aprotic solvent or a protic solvent or a mixture thereof, preferably selected from acetone, ethyl acetate, dimethylformamide, acetonitrile, dimethyl sulfoxide, butyl lactate, propylene carbonate, a polymer of 2-oxacycloheptanone and 2,2-dimethyl-1,3-propanediol, polycaprolactone diol and a mixture thereof.

12. The conductive composition according to any one of claims 1 to 11, wherein the organic solvent is present in an amount of 0.15 to 5 wt%, preferably 0.2 to 2 wt%, based on the total weight of the composition.

13. A cured product of the conductive composition as defined in any one of claims 1 to 12.

14. Use of the conductive composition as defined in any one of claims 1 to 12 as an adhesive in electronic applications, preferably as an adhesive in shingled module photovoltaic applications.

15. A photovoltaic module comprising: A series connected string of two or more solar cells in a shingled pattern with an electrically conductive bond between the two or more solar cells, wherein the electrically conductive bond is formed with the electrically conductive composition as defined in any one of claims 1 to 12 or with the cured product according to claim 13.

16. The photovoltaic module of claim 15, wherein the conductive composition is applied by dispensing, spraying or printing.